2015
DOI: 10.21307/ijssis-2017-853
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Force Of High-Speed Solenoid Valve Based On Correlation Analysis

Abstract: High-speed solenoid valve (HSV) is the heart of electronic control fuel system for diesel engines, whose electromagnetic force (EF) determines the dynamic response speed of fuel system. The finite element model of HSV has been established and validated by experiment. Methods of experimental design and correlation analysis have been used for the simulation experiment. The effect laws of six key parameters' interactions on EF under HSV's overall operating conditions have been revealed from the results of the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…Hung and Lim [12] presented a simulation study to improve the electromagnetic force of a solenoid injector, in which they changed the cross-sectional shape of the coil, thickness of the cut-off of the sleeve, and the relative position between the coil and plunger to obtain the highest electromagnetic force. The improvements of electromagnetic force based on the effects of structural parameters were also found in other studies [13][14][15][16][17][18][19][20][21][22]. The previous studies [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] provided useful information when improving electromagnetic force in a solenoid by optimizing design parameters such as plunger shape, plunger mass, coil shape, coil turns, coil location, air gap, pole radius, and yoke thickness of the magnet.…”
Section: Introductionsupporting
confidence: 58%
“…Hung and Lim [12] presented a simulation study to improve the electromagnetic force of a solenoid injector, in which they changed the cross-sectional shape of the coil, thickness of the cut-off of the sleeve, and the relative position between the coil and plunger to obtain the highest electromagnetic force. The improvements of electromagnetic force based on the effects of structural parameters were also found in other studies [13][14][15][16][17][18][19][20][21][22]. The previous studies [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] provided useful information when improving electromagnetic force in a solenoid by optimizing design parameters such as plunger shape, plunger mass, coil shape, coil turns, coil location, air gap, pole radius, and yoke thickness of the magnet.…”
Section: Introductionsupporting
confidence: 58%
“…Vòi phun điện từ có thể sử dụng trong các loại vòi phun trên động cơ xăng, động cơ diesel, động cơ sử dụng nhiên liệu khí [6-9]. Bên cạnh đó một số kết quả nghiên cứu vòi phun điện từ trên động cơ diesel, ảnh hưởng của điện áp, đường kính cuộn dây đến hiệu suất của lực từ, đã cho thấy thời gian phản hồi của điện từ phụ thuộc vào đường kính dây [10,11]. Trong nghiên cứu của Yin và Wu [12] đã tiến hành xây dựng mô hình toán học và sử dụng phần mềm Matlab-Simulink để xây dựng và mô phỏng hoạt động của vòi phun điện từ sử dụng cho hệ thống phun khí nén.…”
Section: đặT Vấn đềunclassified
“…Their results showed that the response time of the solenoid depended more on the winding number of the wire than on the wire diameter. In a study conducted by De et al [10], the increase of coil turns in a solenoid valve led to greater electromagnetic force. Cvetkovic et al [11] used a modeling approach to develop a high-performance small size solenoid applied for a fuel injector.…”
Section: Introduction *mentioning
confidence: 98%
“…The operating performance of the EPR depends on electromagnetic force of the solenoid valve. The previous studies concentrated on improving the electromagnetic force of solenoids based examination of structural parameters [5][6][7][8][9][10][11][12]. Hung et al [5] ISSN: 2734-9373 https://doi.org/10.51316/jst.152.ssad.2021.31.2.11 Received: December 23, 2020; accepted: May 13, 2021 developed a solenoid applied for a gas injector, in which they varied structural parameters such as plunger mass, spring stiffness, and coil turns to increase the electromagnetic force.…”
Section: Introduction *mentioning
confidence: 99%